To find \((f \cdot g)(x)\), we multiply the two functions \(f(x)\) and \(g(x)\).
Given:
- \(f(x) = x\) (length)
- \(g(x) = x + 3\) (width)
The product \((f \cdot g)(x)\) is calculated as follows:
\[ (f \cdot g)(x) = f(x) \cdot g(x) = x \cdot (x + 3) \]
Now, let's simplify this:
\[ (f \cdot g)(x) = x(x + 3) = x^2 + 3x \]
This result represents the area of the rectangle in square feet, as the area of a rectangle is given by the formula \( \text{Area} = \text{Length} \times \text{Width} \).
So, the correct response is:
\((f \cdot g)(x) = x^2 + 3x\); It represents the area of the rectangle in square feet.